Anticoagulant Activities of Olea Europaea Leaves and Fruit Extract - Sara, Himour; Hayat, Belhain; Mehbouba, Bouketta (European Scientific Journal, ESJ, 2017)
The objective of this study is the evaluation of the anticoagulant activity of polyphenols obtained from extracts of the leaves, and fruits of olive (Olea europaea L.) of four varieties cultivated in the station Maazouzi Lakhdar (Mila, Algeria). The anticoagulant activity of the polyphenolic extracts, of the leaves and fruits of olive have been evaluated in vitro, using the test of Quick time (QT). The values of clotting time a showed a surprising anticoagulant activity on the exogenous pathway of coagulation, significant in the case of leaves and fruits of the Chemlel variety.